The Priority Distribution of Wealth the Debtor’s Bankrupt (Boedel Bankruptcy) Towards Separatist and Preferential of Creditor Based on Principles of Fairness and Legal - . Yuhelson; . Maryano (The Southeast Asia Law Journal, 2016)
Indonesia modern civil law development lasted to align with community life progress. In 1998 made bankruptcy laws reform of colonial legacy, which was revised in 2004 by Law No. 37. Additionally, the bankruptcy law instruments sourced on the Civil Code and some other provisions. After the court decision on bankruptcy declaration, bankruptcy process was arrangement and distribution of wealth the debtor’s bankrupt (boedel bankruptcy) by curator. So far, the difficulty legal curator instrument cared and settled bankruptcy estate. The prioritization of splitting on the preference and separatist creditor. This research was classified as a normative legal research. Basically, the research based on secondary data. The research conclusion, first, completion of settlement the boedel bankruptcy arranged which reflected in a series of activities that sequence according to the stages and institutionally involve the creditor committee, curator, and the supervisory judge; second, the principles of justice that could be applied in determining the division of boedel bankruptcy to creditors, particularly the preferred and separatist creditors, namely the principle of pari passu and pro rata, the principle of balance, the principle of proportional, and the principles of fairness; third, instruments of Indonesia bankruptcy law consists of elements of civil law (Civil Code), bankruptcy law and suspension of debt payments (Act No. 37 of 2004), a variety of laws and regulations under the law, occasionally based on the policy elements. This condition reduces the level of security in the application of the law.Keywords: bankruptcy, boedel bankruptcy, preferred creditors, separatist creditors